Sub aortic fibro muscular ridge with congenital bicuspid aortic valve - Kumar, J. Rajendra; Kumbhare, Mamta B.; Nazneen, Shabana (International Journal of Research in Medical Sciences, 2017)
Congenital bicuspid aortic valve stenosis is estimated to occur in 1 to 2% of general population, making it the single most common congenital cardiac anomaly, but in association with fibro muscular sub aortic ridge (fibro muscular collar) is a rare combination of congenital cardiac anomalies. We present here a rare case of sub aortic fibro muscular ridge that is associated with congenital bicuspid aortic valve.